2014
DOI: 10.1128/aac.03613-14
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine Induces Downregulation of Mitochondrial Deoxynucleoside Kinases: Implications for Mitochondrial Toxicity of Antiviral Nucleoside Analogs

Abstract: Mitochondrial thymidine kinase 2 (TK2) and deoxyguanosine kinase (dGK) catalyze the initial phosphorylation of deoxynucleosides in the synthesis of the DNA precursors required for mitochondrial DNA (mtDNA) replication and are essential for mitochondrial function. Antiviral nucleosides are known to cause toxic mitochondrial side effects. Here, we examined the effects of 3=-azido-2=,3=-dideoxythymidine (AZT) (zidovudine) on mitochondrial TK2 and dGK levels and found that AZT treatment led to downregulation of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…Next, we sought to determine whether the over‐reliance of lung CSC on DGUOK could be exploited to inhibit tumor growth and to prevent tumor initiation. There is currently no specific DGUOK inhibitor available; however, several FDA‐approved anti‐HIV reverse transcriptase inhibitors such as didanosine (DDI) and zidovudine have been shown to inhibit DGUOK and mtDNA homeostasis in cell culture and mouse models (Sun et al , ,c). Interestingly, there is anecdotal evidence that DDI treatment might be responsible for the long‐term survival in a HIV‐positive small‐cell lung cancer patient (Kato et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we sought to determine whether the over‐reliance of lung CSC on DGUOK could be exploited to inhibit tumor growth and to prevent tumor initiation. There is currently no specific DGUOK inhibitor available; however, several FDA‐approved anti‐HIV reverse transcriptase inhibitors such as didanosine (DDI) and zidovudine have been shown to inhibit DGUOK and mtDNA homeostasis in cell culture and mouse models (Sun et al , ,c). Interestingly, there is anecdotal evidence that DDI treatment might be responsible for the long‐term survival in a HIV‐positive small‐cell lung cancer patient (Kato et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is currently no specific DGUOK inhibitor available, several reports indicated that FDA‐approved anti‐HIV reverse transcriptase inhibitors such as DDI and zidovudine could also inhibit DGUOK and TK2 (Sun et al , ,c). Indeed, it was reported that HIV‐infected patients receiving DDI treatment displayed 47% decrease in mtDNA copies in liver biopsies (Walker et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma concentrations of 50μM have been observed for AZT in the clinic [ 32 ]. In vitro experiments commonly use concentrations between 10–200μM [ 11 , 74 , 75 ]. Drugs can be exposed to nematodes on solid media, by either mixing them in with the bacterial lawn or adding them directly to the agar plates [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the individuals who were administered a placebo, AZT patients had significantly more cases of anemia and neutropenia as well as more AZT patients needed red-cell transfusions compared to the placebo group 40 . It has also been reported that AZT decreases cell viability in vitro 41 and induces mitochondrial toxicity at physiological concentrations [42][43][44] . As years passed, ART improved, with decreases in toxicity shown in NRTIs TFV, emtricitabine (FTC), and lamivudine (3TC) compared to other commonly prescribed ART such as AZT, didanosine (ddI), ritonavir (RTV), lopinavir (LPV), and stavudine (d4T) 45,46 .…”
Section: Early Toxic Effectsmentioning
confidence: 95%
“…ROS have also been shown to be important signaling molecules, critical to inflammatory and antiviral immune responses, especially in TLR4 signaling and immune activation 256 . Superoxides, the main type of mitochondrial ROS, are produced from the reduction of oxygen by one electron, which leak out of the ETC 43 . Superoxides are produced mainly through ETC complexes I and III, and are used mainly in signaling pathways or to combat invading pathogens, but also have toxic abilities if they accumulate 119,120 .…”
Section: Superoxide and Total Cellular Ros Productionmentioning
confidence: 99%